Treatment of knee joint osteoarthritis in overweight women in outpatient practice - P. S. Kovalenko; I. S. Dydykina; E. S. Aronova; O. G. Alekseeva; E. L. Shakhramanova; A. V. Kudryavtseva; E. G. Zotkin (Современная ревматология)
Objectives: evaluation of the clinical efficacy and safety of the healthy joints maintaining compound Artroflex® in knee osteoarthritis (OA) in postmenopausal overweight women in outpatient clinical practice.Patients and methods. An open, prospective observational single-center post-marketing study included 30 postmenopausal women 50–75 years old (mean age 62.3±6.3 years) with knee OA. Patient body mass index (BMI) was >25 (mean body weight 85.3±15.3 kg). Radiographically confirmed primary gonarthrosis stage II according to Kellgren–Lawrence was detected in 26 (87.0%) patients, stage III – in 4 (13.0%). The duration of knee OA ranged from 1 to 21 years (average 7.8±6.1 years).Artroflex® was prescribed 1 capsule 2 times a day for 3 months. During three visits (baseline, after 1 and 3 months), the need for analgesics or non-steroidal anti-inflammatory drugs (NSAIDs) and the occurrence of adverse reactions (AR) were determined. Health status and pain level were also assessed using a visual analogue scale (VAS), the severity of pain and stiffness, limited function according to the WOMAC questionnaire, fatigue/fatigue according to the FACIT scale, the Charlson comorbidity index, satisfaction of the doctor with the results of treatment using the IMOS scale, and satisfaction of the patient with using the IMPSS scale.Results and discussion. A statistically significant decrease in the pain score according to the VAS, an improvement in health status, and the WOMAC index were found in the overwhelming number of patients, regardless of BMI. 90% of women noted decrease in fatigue/fatigue on the FACIT scale, and 93% of patients reported satisfaction with treatment, regardless of the Charlson comorbidity index. The need for NSAIDs after one month of use of the Artroflex® compound decreased by 7%, after 3 months – by 23%. A negative feedback was found between the baseline indicator of health status and the assessment of the effectiveness of therapy. No serious ARs were identified during the study.Conclusion. Feasibility of using the Artroflex® compound in real clinical practice in patients with knee OA and excessive body mass has been shown.